Psychological and Social Dynamics of Cyberbullying Victims: An Analysis of the Impact on Middle School Students - Wulandari, Tri Putri; Sujarwo, Sawi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The advancement of communication technology has facilitated social interactions but has also opened the door to bullying behaviors that are harder to detect. Cyberbullying differs from conventional bullying as perpetrators can launch attacks through various social media platforms, forums, and messaging applications. This research aimed to analyze and understand the psychological and social dynamics experienced by victims of cyberbullying among middle school students, and to identify the impacts of these experiences on their emotional well-being, social interactions, and psychological development. A qualitative approach was used, allowing the researcher to grasp the dynamics experienced by the subjects. Victims of cyberbullying were found to experience similar negative effects, starting from disturbances at school that extended to social media. These negative impacts included feelings of deep hurt, loss of self-confidence, social rejection, and a desire for revenge. However, a positive impact was also identified, in the form of increased motivation to surpass the bully. The implications of this study highlight the need for more comprehensive school policies and proactive measures to effectively address cyberbullying.Perkembangan teknologi komunikasi semakin memudahkan interaksi sosial, namun di sisi lain juga membuka peluang bagi perilaku bullying yang lebih sulit terdeteksi. Cyberbullying berbeda dari bentuk bullying konvensional karena pelaku dapat melancarkan serangan melalui berbagai platform media sosial, forum, dan aplikasi pesan singkat. untuk menganalisis dan memahami dinamika psikologis dan sosial yang dialami oleh korban cyberbullying di kalangan peserta didik Sekolah Menengah Pertama, serta mengidentifikasi dampak yang timbul dari pengalaman tersebut terhadap kesejahteraan emosional, interaksi sosial, dan perkembangan psikologis. Penelitian ini menggunakan pendekatan kualitatif, yang memungkinkan peneliti memahami gambaran dinamika subjek. korban cyberbullying mengalami dampak yang serupa dengan gangguan yang dimulai di lingkungan sekolah dan kemudian meluas ke media sosial. Dampak negatif yang dirasakan termasuk perasaan sakit hati, hilangnya kepercayaan diri, penolakan sosial, dan keinginan untuk membalas dendam. Namun, dampak positif berupa peningkatan motivasi untuk menjadi lebih baik dari pelaku juga ditemukan. Implikasi dari penelitian ini menunjukkan perlunya kebijakan dan tindakan yang lebih komprehensif dari pihak sekolah dalam menangani cyberbullying secara proaktif.